2016
DOI: 10.1038/srep26093
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Role of H19 Contributing to Cisplatin Resistance by Regulating Glutathione Metabolism in High-Grade Serous Ovarian Cancer

Abstract: Primary and acquired drug resistance is one of the main obstacles encountered in high-grade serous ovarian cancer (HGSC) chemotherapy. Cisplatin induces DNA damage through cross-linking and long integrated non-coding RNAs (lincRNAs) play an important role in chemical induced DNA-damage response, which suggests that lincRNAs may be also associated with cisplatin resistance. However, the mechanism of long integrated non-coding RNAs (lincRNAs) acting on cisplatin resistance is not well understood. Here, we showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 51 publications
7
92
0
Order By: Relevance
“…LUCAT1 has also been reported as a liver metastasis‐associated lncRNA through an analysis of CRC tissues from TCGA and Gene Expression Omnibus (GEO) databases; however, the underlying mechanisms are still unclear. Consistent with other studies, in which some lncRNAs including LUCAT1 are associated with chemotherapy resistance, our results revealed that LUCAT1 knockdown enhanced the apoptosis of CRC cells treated with oxaliplatin and 5‐FU.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…LUCAT1 has also been reported as a liver metastasis‐associated lncRNA through an analysis of CRC tissues from TCGA and Gene Expression Omnibus (GEO) databases; however, the underlying mechanisms are still unclear. Consistent with other studies, in which some lncRNAs including LUCAT1 are associated with chemotherapy resistance, our results revealed that LUCAT1 knockdown enhanced the apoptosis of CRC cells treated with oxaliplatin and 5‐FU.…”
Section: Discussionsupporting
confidence: 92%
“…Lung cancer‐associated transcript 1 is located on chromosome 5 and was first observed in the airway epithelium of smokers and in various cancer cell lines . In addition to lung cancer, LUCAT1 has also been reported to be involved in esophageal cancer, renal cell carcinoma, and cisplatin‐resistant ovarian cancer . Like other lncRNAs, LUCAT1 participates in carcinogenesis and cancer progression by regulating gene expression through chromatin modification, transcription, and post‐transcriptional procession.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical samples analysis showed that higher expression of LUCAT1 was associated with tumor size, tumornode-metastasis (TNM) stage and overall survival (OS). Besides, LUCAT1 also showed to modulate drug resistance [23,24]. To explore the potential molecular mechanisms of these lncRNA, we used GO and pathway analyses.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] Our previous study revealed that H19 expression level, associated with its promoter methylation status, was significantly upregulated in CML patients involving in disease progression. 11,21 Therefore, it is important to illuminate the resistance mechanism and to overcome H19 is a long chain non-coding RNA with length of 2.3 kb.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that overexpression of H19 was correlated with drug resistance in many tumors such as lung adenocarcinoma, ovarian cancer, human glioma, liver cancer. [31][32][33][34] Our previous study revealed that H19 expression level, associated with its promoter methylation status, was significantly upregulated in CML patients involving in disease progression. 35 Also, H19 was identified to be upregulated by DDX43 through demethylation related to CML progression.…”
Section: Discussionmentioning
confidence: 99%